The origin of Late Devonian (Frasnian) stratiform and stratabound mudstone-hosted barite in the Selwyn Basin, Northwest Territories, Canada. (August 2017) - Fernandes, Neil A.; Gleeson, Sarah A.; Magnall, Joseph M.; Creaser, Robert A.; Martel, Edith; Fischer, Beth J.; Sharp, Robert
Abstract: Multiple occurrences of bedded barite (BaSO4 ) are preserved in mudstones of the upper-most Canol Formation (Frasnian) of the Selwyn Basin (Canada). Samples of barite were collected from eight sites (seven measured sections), and examined using petrographic and isotopic techniques ( 87 Sr/ 86 Sr, δ 34 S and δ 18 O values) to determine whether the barite has a diagenetic or hydrothermal origin. Barite at all locations occurs in two morphologies: (1) laminated barite composed of thin layers of microcrystalline barite with lesser amounts of pyrite and hyalophane (Ba-K-feldspar) interlaminated with mudstone, and (2) nodular barite consisting of barite, hyalophane, cymrite (hydrous Ba-silicate) and minor pyrite. At the Cowan occurrence, one sample has a mineral assemblage comprising barite and nodular barium carbonates (witherite, norsethite). The δ 34 S and δ 18 O values of the laminated barite co-vary, and range between +24.1 and +35.3‰ and +14.8 to +18.3‰ respectively, with the exception of one sample with δ 34 S and δ 18 O values of +32.9‰ and −0.5‰. The laminated samples have an average 87 Sr/ 86 Sr of 0.7085 (n = 8), which is consistent with Frasnian seawater (0.7081) that has undergone some minor water sediment interaction during early diagenesis. The nodular barite has highly variable δ 34 S (+4.8 to +56.5‰) and δ 18 O (+9.2 to +19.3‰) values, which developed from more evolved diagenetic pore fluids with limited sulphate re-supply (i.e., as a relatively closed system). In these conditions sulphate reduction likely occurred at a slower rate, and the sulphate in the barite records both kinetic (δ 34 SSO4 ) and equilibrium (δ 18 OSO4 ) isotope effects. One sample of nodular barite has a 87 Sr/ 86 Sr ratio of 0.7086. The single sample with a barite and barium-carbonate assemblage at Cowan has a 87 Sr/ 86 Sr ratio of 0.7133, a δ 34 S value of +23.9‰, and a δ 18 O value of +10.7‰ and may represent a local hydrothermal event at this site. Our data supports the interpretation that the barite horizon is a stratigraphic marker throughout the Canol Formation. Laminated and nodular barite formed as a result of diagenetic processes, which recycled Ba from organic matter in the sediment below, and reprecipitated it above, the sulphate methane transition zone in the sediments. The results of this study are similar to those obtained for other Late Devonian sediment-hosted barite occurrences in North America (Yukon, Nevada, New York State), meaning these occurrences likely formed by similar processes and diagenetic pore water conditions within oceanic sediments that covered the North American continent during the Late Devonian. We suggest that the combination of high biological productivity and low seawater sulphate at this time contributed to the efficient cycling of Ba from seawater into the sediments on the continental margin. Highlights: Frasnian stratabound barite beds have a diagenetic origin. Nodular and laminated barite textures formed at a fluctuating sulphate methane transition zone. Units are a marker horizon in the Selywn Basin. Formed as a result of low seawater sulphate and high biological productivity.